2020
DOI: 10.1088/2516-1091/abaaa3
|View full text |Cite
|
Sign up to set email alerts
|

Optical spectroscopy for in vivo medical diagnosis—a review of the state of the art and future perspectives

Abstract: When light is incident to a biological tissue surface, combinations of optical processes occur, such as reflection, absorption, elastic and non-elastic scattering, and fluorescence. Analysis of these light interactions with the tissue provides insight into the metabolic and pathological state of the tissue. Furthermore, in vivo diagnosis of diseases using optical spectroscopy enables in situ rapid clinical decisions without invasive biopsies. For in vivo scenarios, incident light can be delivered in a highly l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 49 publications
(26 citation statements)
references
References 326 publications
0
26
0
Order By: Relevance
“…Thus, Raman spectroscopy provides chemical fingerprints of biological materials such as cells, tissues or biological fluids through inelastic scattering of light by vibrating molecules [58,102,103]. This fingerprint represents molecular vibrations brought about by chemical bonds, thus deciphering the samples chemical or biochemical composition.…”
Section: Application Of Raman Spectroscopy In In-vivo Diagnosticsmentioning
confidence: 99%
“…Thus, Raman spectroscopy provides chemical fingerprints of biological materials such as cells, tissues or biological fluids through inelastic scattering of light by vibrating molecules [58,102,103]. This fingerprint represents molecular vibrations brought about by chemical bonds, thus deciphering the samples chemical or biochemical composition.…”
Section: Application Of Raman Spectroscopy In In-vivo Diagnosticsmentioning
confidence: 99%
“…The modified frame work of tetrahedral DNA nano-probes with peptides targeting and malignant glioma and both brain capillary endothelial cells. A study suggested that the DNA nanoprobes successfully passed via the BBB model and then entered the cytoplasm of the tumor cells [ 213 ]. Despite the prominent selectivity in vitro some ligands lose targeting capacity in vivo.…”
Section: Biosafety/biocompatibility Stability and Targeting Capacity For In Vivo Applicationsmentioning
confidence: 99%
“…Optical techniques have traditionally been performed in clinical procedures for decades [ 116 , 117 , 118 ]. From a medical point of view, the different existing optical biopsy techniques offer a detailed tissue fingerprint based on its chemical content [ 117 , 119 ].…”
Section: Fibre-optical Probes For Needles Catheters and Endoscopymentioning
confidence: 99%